Examining The Mediation Of Trust and Reputation In the Relationship Between Transaction Security And Purchase Intention - Anna Wulandari; Heru Mulyanto (Fakultas Ekonomi dan Bisnis Islam, 2025)
This study explores the mediating roles of trust and reputation in the relationship between transaction security and purchase intention on Shopee. As online shopping becomes increasingly common, understanding how security influences consumer behavior is essential for e-commerce growth. The research investigates how transaction security affects purchase intention through trust and reputation, addressing the question: How does transaction security influence purchase intention via trust and reputation on Shopee? This study offers novelty by analyzing trust and reputation simultaneously as mediators an approach rarely explored together in existing research. Using a quantitative method and structural equation modeling (SEM), data were collected from 161 Shopee users. The results show that transaction security significantly increases both trust and reputation. However, while reputation positively affects purchase intention, trust alone does not show a significant direct influence. The findings imply that improving transaction security must be accompanied by strong reputation management to effectively drive consumer purchasing decisions. For platforms like Shopee, integrating security measures with visible, trustworthy reputation systems is key to enhancing user confidence and boosting engagement. The study concludes that robust transaction security must be complemented by effective reputation management to increase purchase intention. Ecommerce platforms like Shopee should prioritize both security protocols and user reputation systems to foster consumer confidence and drive engagement.